Volume do tronco de corymbia citriodora empregando o método da altura relativa - Terra, David Lucas Camargo Vieira (Universidade Federal do Tocantins, 2017)
In this study, evaluate the control models to describe the profile of the Corymbia citriodora. The data used are obtained from a commercial plant located in the southern region of the state of Tocantins. There are data from 24 Corymbia citriodora trees accurately cubed with diameter measurements in stem families: 0.2; 0.4; 0.7; 1,3; 2.70 m and, successively, from 2 m in 2 m to a diameter of around 3 cm in shell. 44 taper models were tested, being 25 linear and 19 nonlinear. In the evaluation of these models, we consider an analysis of the distribution of residues, and statistics: standard error of estimation, coefficient of determination, randomized block design with split plot arrangement, mean absolute deviation, square root of mean error, sum of squares of residuals, standard deviation of the differences, Akaike's information criterion. The bestperforming model for an exponent-shape fit type adjusted in nonlinear form. This version has a long list of corrections, changes, and new developments that significantly improve functioning. In this comparison, statistical criteria are used: mean deviation, bias, linear correlation, standard error of the estimate, between observed and estimated values, precision, obtained by square test and square root of error, as well as analysis of distribution and residues. It was concluded that the use of a cube simulated by the method of elevation of the estimate, as well as a conciliation equation as one obtains by the use of real data.